Characterization and transmission of plasmid-mediated multidrug resistance in foodborne Vibrio parahaemolyticus - Zhou, Haibo; Lu, Zhaoxin; Liu, Xinmei; Bie, Xiaomei; Cui, Xinping; Wang, Zuwei; Sun, Xiaojie; Yang, Jun (Frontiers in Microbiology, 2024)
Objectives The purpose of this study was to determine the structural features and transferability of the multidrug-resistance (MDR) plasmid, and resistance phenotypes for the tested antimicrobials in foodborne Vibrio parahaemolyticus. Methods Plasmids were isolated from a V. parahaemolyticus strain of seafood origin, then sequenced using the Illumina NovaSeq 6000 and PacBio Sequel II sequencing platforms to obtain the complete genome data. Characterization of the MDR plasmid pVP52-1, including determination of antimicrobial resistance genes (ARGs), plasmid incompatibility groups, and transferability, was carried out. Results V. parahaemolyticus strain NJIFDCVp52 contained two circular chromosomes and two circular plasmids (pVP52-1 and pVP52-2). Plasmid typing indicated that pVP52-1 belonged to the incompatibility group IncA/C2 and the sequence type pST3. pVP52-1 carried 12 different ARGs, an IS110-composite transposon consisting of aac(6′)-Ib-cr, qnrVC1, aac(6′)-Ib, dfrA14, and the IS26-mphA-IS6100 unit flanked by inverted sequences of IS5075 and IS4321. pVP52-2 carried no ARGs. A plasmid elimination assay showed that only pVP52-1 and its ARGs were lost, the loss of resistance to several antimicrobials, causing a change from the ampicillin-ampicillin/sulbactam-cefazolin-cefoxitin-ceftazidime-cefotaxime-imipenem-trimethoprim/sulfamethoxazole resistance pattern to the ampicillin resistance pattern. In accordance, a conjugation transfer assay showed that only pVP52-1 and its ARGs were horizontally transferred, leading to increased antimicrobial resistance in Escherichia coli strain EC600, causing a change from the ampicillin-nalidixic acid resistance pattern to the ampicillin-ampicillin/sulbactam-cefazolin-cefoxitin-ceftazidime-cefotaxime-imipenem-nalidixic acid-chloramphenicol-tetracycline-trimethoprim/sulfamethoxazole-azithromycin resistance pattern. Further transferability experiments revealed that pVP52-1 could be transferred to other enterobacterial strains of E. coli and Salmonella. Discussion This study emphasizes the urgent need for continued surveillance of resistance plasmids and changes in antimicrobial resistance profiles among the V. parahaemolyticus population.